How "Us" and "Them" Relates to Voting Behavior—Social Structure, Social Identities, and Electoral Choice. (October 2021) - Bornschier, Simon; Häusermann, Silja; Zollinger, Delia; Colombo, Céline
The last decades have seen the emergence of a divide pitting the new left against the far right in advanced democracies. We study how this universalism-particularism divide is crystallizing into a full-blown cleavage, complete with structural, political and identity elements. So far, little research exists on the identities that voters themselves perceive as relevant for drawing in- and out-group boundaries along this divide. Based on an original survey from Switzerland, a paradigmatic case of electoral realignment, we show that voters' "objective" socio-demographic characteristics relate to distinctive, primarily culturally connoted identities. We then inquire into the degree to which these group identities have been politicized, that is, whether they divide new left and far right voters. Our results strongly suggest that the universalism-particularism "cleavage" not only bundles issues, but shapes how people think about who they are and where they stand in a group conflict that meshes economics and culture.